2019
DOI: 10.1029/2018gl081804
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Magnetic Reconnection in the Transition Region of Quasi‐Parallel Shocks

Abstract: Using observations of Earth's bow shock by the Magnetospheric Multiscale mission, we show for the first time that active magnetic reconnection is occurring at current sheets embedded within the quasi‐parallel shock's transition layer. We observe an electron jet and heating but no ion response, suggesting we have observed an electron‐only mode. The lack of ion response is consistent with simulations showing reconnection onset on sub‐ion time scales. We also discuss the impact of electron heating in shocks via r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 41 publications
6
71
1
Order By: Relevance
“…• In a quasi-parallel shock, guide field reconnection occurs in the shock transition and downstream regions • In electron-scale islands, only electron jets exist in reconnection, producing a Hall magnetic field pattern • In ion-scale islands, both ions and electrons are involved and energized in reconnection ion jets were observed. Gingell et al (2019) studied two quasi-parallel shocks and showed reconnecting current sheets with only electron outflow jets in the transition region.…”
Section: 1029/2019gl083397mentioning
confidence: 99%
See 1 more Smart Citation
“…• In a quasi-parallel shock, guide field reconnection occurs in the shock transition and downstream regions • In electron-scale islands, only electron jets exist in reconnection, producing a Hall magnetic field pattern • In ion-scale islands, both ions and electrons are involved and energized in reconnection ion jets were observed. Gingell et al (2019) studied two quasi-parallel shocks and showed reconnecting current sheets with only electron outflow jets in the transition region.…”
Section: 1029/2019gl083397mentioning
confidence: 99%
“…In one event, an ion‐scale sheet showed only electron jets, while in another current sheet whose thickness is several ion skin depths, both electron and ion jets were observed. Gingell et al () studied two quasi‐parallel shocks and showed reconnecting current sheets with only electron outflow jets in the transition region.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of reconnection has been reported to occur in the magnetosheath downstream of the Earth's bow shock Phan et al, 2018;Retinò et al, 2007;Vörös et al, 2017;Wilder et al, 2017Wilder et al, , 2018. Features of current sheet structures consistent with magnetic reconnection were identified in the transition region of a quasi-parallel shock in a recent study (Gingell et al, 2018). The role of reconnection in energy conversion in the shock and differences and similarities between the reconnection features at the shock and those in magnetotail and magnetopause are yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we analyze four reconnection events, which were observed recently at the terrestrial bow shock by Gingell et al () and Wang, Chen, et al (), using the FOTE method. We find radial nulls (X‐line) in three events, which were identified as diffusion regions.…”
Section: Discussionmentioning
confidence: 99%
“…The third event, detected by MMS at about 06:07:02 UT on 31 December 2016, has been analyzed by Gingell et al (2019) and identified as a reconnection diffusion region at the quasi-parallel bow shock. Figure 2C is in the same format as Figure 2A (Panels b and d), indicating the existence of "inplane" magnetic nulls in this event.…”
Section: Observationsmentioning
confidence: 99%